Race, Space, and Culture: Exploring the Educational Experiences of African American Doctoral Social Work Students. - Bryant, Danté D.; Swafford, Tayon (Journal of Social Work Education)
In 2008, the Council on Social Work Education (CSWE) initiated internal efforts to reenvision its accreditation framework. One of its primary intentions was to identify and engage in activities that could further advance racial equity throughout social work education. However, despite these efforts, CSWE's focus and effect have been largely relegated to bachelor's- and master's-level programs. Conversely, considerably less attention has been dedicated to exploring the potential need for similar pursuits within doctoral-level social work spaces. To respond to this gap in the literature, this study engages the experiential realities of 14 African American social work doctoral students attending predominantly White collegiate institutions. This study uses interpretative phenomenological analysis and the concept of race and space to understand, articulate, and contextualize better the educational experiences of the largest racialized population within social work doctoral programs. Major findings suggest shared experiences of cultural estrangement, distrust, and protective distancing. Findings have significant implications for social work education and research and may inform efforts to more fully advance doctoral educational environments to ensure their promotion and embodiment of social work's professed commitment to actualizing more racially and culturally just institutional practices, policies, and procedures.